Bourdieu and Sociological Biography: The Case of Vincent van Gogh's Choice of Profession. (October 2022) - Atkinson, Will
Pierre Bourdieu's conceptual framework offers a productive means of making sense of statistical regularities and correspondences. When it comes to explaining the intricacies of individual biographies, however, including something as seemingly personal as one's choice of occupation, Bourdieu offers only a starting point in need of elaboration. Above all, there is a need to pay greater attention to the multiplicity of fields in which individuals are situated and the interplay between them in shaping desires and strategies. These include class, family relations and, in some cases, employment-based fields such as art, religion or specific organisations. To demonstrate the argument, this article takes as a case study the trajectory of Vincent van Gogh, highlighting the ongoing interaction between class, family and other fields in generating his eventual decision to become an artist.